Alternatives to the use of the crowbar circuit in DFIG based wind turbines during balanced voltage dips. - Avila Naranjo, Rafael Ricardo (2014)
Most of the modern wind turbines are based on doubly fed induction generators (DFIG), with a back to back power converter connecting the rotor to the network. It is known that voltage dips at the stator terminals can cause overcurrents in the rotor windings, which could threaten the converter integrity. In order to protect the converter, several strategies have been proposed in technical literature, requiring in some cases the converter deactivation, which disables the control that the converter has over the power transference between the generator and the system. This last is not a desirable behavior since it can put on risk the voltage stability of the electric system. It is the aim of this dissertation to introduce and compare five of those protection strategies, through the computational simulation of their performance in case of balanced voltage dips. In order to achieve this, the electromagnetic dynamic model of the DFIG was theoretically developed, as well as the models of the strategies of interest. Subsequently, the computational model of the system was assembled in the software Matlabs Simulink to finally perform the desired simulations and its corresponding analysis.